2008
DOI: 10.1111/j.1558-5646.2008.00376.x
|View full text |Cite
|
Sign up to set email alerts
|

Learning Ability and Longevity: A Symmetrical Evolutionary Trade-Off in Drosophila

Abstract: Learning ability can be substantially improved by artificial selection in animals ranging from Drosophila to rats. Thus these species have not used their evolutionary potential with respect to learning ability, despite intuitively expected and experimentally demonstrated adaptive advantages of learning. This suggests that learning is costly, but this notion has rarely been tested. Here we report correlated responses of life-history traits to selection for improved learning in Drosophila melanogaster. Replicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
103
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 110 publications
(111 citation statements)
references
References 65 publications
6
103
1
1
Order By: Relevance
“…longer-lived butterflies should repeatedly employ their learning abilities, enabling them to gain more benefits than costs of learning. Such costs of learning have been reported in fruit flies, whereby flies from lines selected for improved learning ability had reduced larval competitive ability (Mery and Kawecki, 2003), lower egg-laying rates (Mery and Kawecki, 2004) and decreased lifespan (Burger et al, 2008) compared with flies from unselected lines.…”
Section: Learning Rate Differences In Butterfliesmentioning
confidence: 99%
“…longer-lived butterflies should repeatedly employ their learning abilities, enabling them to gain more benefits than costs of learning. Such costs of learning have been reported in fruit flies, whereby flies from lines selected for improved learning ability had reduced larval competitive ability (Mery and Kawecki, 2003), lower egg-laying rates (Mery and Kawecki, 2004) and decreased lifespan (Burger et al, 2008) compared with flies from unselected lines.…”
Section: Learning Rate Differences In Butterfliesmentioning
confidence: 99%
“…Kolss & Kawecki [72] artificially selected flies for adaptation to larval nutritional stress over several generations and observed a decrease of learning ability in selected lines when compared with control lines. Using a similar approach, Burger et al [73] described a symmetrical trade-off in Drosophila between learning ability and adult longevity. By contrast, a recent study [74] showed a positive relationship in honeybees between learning ability and resistance to oxidative stress resistance, which is often related to overall longevity, and Bombus terrestris shows a positive relationship between learning ability and antibacterial immune response at the colony level [75].…”
Section: Experimental Evidence For a Cost Of Learning And Memory In Imentioning
confidence: 99%
“…The energetic constraints are not negligible. Larger brains and more neurons incur a higher metabolic cost than smaller brains [15] and have been shown to result in shorter life spans and lower fecundity in late life (e.g., in Drosophila, [16]). …”
Section: Energetic Constraintsmentioning
confidence: 99%